A new species of Pterygonema (Nematoda: Ceramonematoidea) from sublittoral sand in Liverpool Bay - Ward, A. R. (Marine Biology, 1973)
Locality: Liverpool Bay; Cabinet:
Locality: Liverpool Bay; Cabinet:; NeMys doc_id: 7380